The role of low molecular weight organic acids in release kinetics of zinc and cadmium in polluted calcareous soil in the presence of fish scales derivatives. Issue 1 (2nd January 2021) - Ghasemi-Fasaei, Reza; Paridar, Zeynab; Ronaghi, Abdolmajid
ABSTRACT: Immobilisation is an effective technique in the remediation of heavy metals polluted soils. A laboratory experiment was conducted to clarify the kinetics of Zn and Cd release using citric, oxalic, acetic and tartaric acids and to evaluate the effectiveness of fish scale powder (FSP), chitin (CTN) and chitosan (CTS) in the immobilisation of these metals in a calcareous soil exposed to high levels of Zn and Cd. Characterisation of Fourier-transform infrared spectroscopy (FTIR) revealed the presence of amines, amides, alkenes and phosphate esters in fish scale and its derivatives. Citric acid released Zn and Cd much higher than tartaric, acetic and oxalic acids. Addition of fish scales derivatives drastically decreased the cumulative release of Zn and Cd in the order of CTS> CTN> FSP. Zn release data well fitted to pseudo-second-order model only in the presence of citric and tartaric acid and to Elovich model in the presence of acetic and oxalic acids. Cd release data were mostly fitted to pseudo-second-order model followed by Elovich model. Results of the present study demonstrate the high capability of citric acid in releasing metals, and high effectiveness of fish scales derivatives especially chitosan in immobilising Cd and Zn in polluted soils.